(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The main task of a future educator is to develop value-based attitudes in students, as the foundation of pedagogical activity is the formation of the moral consciousness of the younger generation. This article analyzes the pedagogical and psychological features of shaping value-based attitudes in students. It emphasizes the importance of educators’ understanding of these values and their ability to foster them through interpersonality-based pedagogical processes. The study highlights key aspects, including the educator’s role in understanding students’ emotions and behavior, and how these impact value formation. Further, the article discusses theoretical frameworks and practical strategies for effectively instilling these values.